THE EFFECT OF DRILLING DIAMETER AND CUTTING SPEED ON THE MACHINABILITY DURING DRILLING MAGNESIUM ALLOYS - CHENG WYEI YEE, SHARON (IRC, 2017)
In the recent industry, magnesium alloys are always preferred for low weight but high strength applications. This study investigates the effect of the drilling diameter and cutting speed on the machinability during drilling magnesium alloys. It provides further data and recommendations to aid machinists and engineers in future magnesium applications. Nine sets of experiments were conducted using three drilling diameters (6mm, 8mm and 10mm) and three cutting speeds (60m/min, 90m/min and 120m/min), resulting in a total of 45 holes drilled into 15mm thick magnesium workpieces. The results are compared in terms of the material removal rate, the final hole diameter, the surface roughness of the hole, the type of chip produced and the level of tool wear. The finding states that when drilling diameter is decreased, hole diameter error, surface roughness, flank wear and crater will decrease. The chips produced will be smaller and well broken and fewer workpiece deposit will be present. The chisel edge wear, however, will increase with decreasing drilling diameter. Cutting speed has no effect on the hole diameter error. When the cutting speed is decreased, chips produced will be larger and curled, chisel edge wear will be higher but produce fewer workpiece deposits, lower flank wear and lower crater wear. Material removal rate increased with increased drilling diameter and cutting speed.